Platelet-Rich Plasma for Patellar Tendinopathy: A Randomized Controlled Trial of Leukocyte-Rich PRP or Leukocyte-Poor PRP Versus Saline. Issue 7 (June 2019) - Scott, Alex; LaPrade, Robert F.; Harmon, Kimberly G.; Filardo, Giuseppe; Kon, Elizaveta; Della Villa, Stefano; Bahr, Roald; Moksnes, Havard; Torgalsen, Thomas; Lee, Jenny; Dragoo, Jason L.; Engebretsen, Lars
Background: A small number of randomized controlled trials have found ultrasound-guided injection of platelet-rich plasma (PRP) to be no more effective than saline for several tendinopathies; limited information exists for patellar tendinopathy. In addition, different PRP formulations that produce varying concentrations of leukocytes have not been directly compared for patellar tendinopathy. Purpose/Hypothesis: To determine if a single ultrasound-guided PRP injection, either leukocyte-rich PRP (LR-PRP) or leukocyte-poor PRP (LP-PRP), was superior to saline injection for the treatment of patellar tendinopathy. The null hypothesis was that no treatment would be superior to another for the treatment of patellar tendinopathy. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Athletes with patellar tendinopathy for ≥6 months (Blazina stage IIIB) were assessed for eligibility in a multisite single-blind controlled trial. There were 3 injection arms: LR-PRP, LP-PRP, and saline. Patients received a single ultrasound-guided injection, followed by 6 weeks of supervised rehabilitation (heavy slow resistance training, concentric and eccentric, 3 times per week). Outcome measures—Victorian Institute of Sport Assessment (patellar; VISA-P), pain during activity, and global rating of change—were assessed at 6 and 12 weeks and 6 and 12 months. VISA-P score at 12 weeks was the primary outcome. Fifty-seven patients (19 in each group) were included in an intention-to-treat analysis. Secondary outcome measures included pain during activity and patients' global rating of change. Results: Study retention was 93% at 12 weeks and 79% after 1 year. There was no significant difference in mean change in VISA-P score, pain, or global rating of change among the 3 treatment groups at 12 weeks or any other time point. After 1 year, the mean (SD) outcomes for the LR-PRP, LP-PRP, and saline groups were as follows, respectively: VISA-P—58 (29), 71 (20), and 80 (18); pain—4.0 (2.4), 2.4 (2.3), and 2.0 (1.9); global rating of change—4.7 (1.6), 5.6 (1.0), and 5.7 (1.2) ( P > .05 for all outcomes). Conclusion: Combined with an exercise-based rehabilitation program, a single injection of LR-PRP or LP-PRP was no more effective than saline for the improvement of patellar tendinopathy symptoms. Registration: NCT02116946 (ClinicalTrials.gov identifier).